2000
DOI: 10.1038/76014
|View full text |Cite
|
Sign up to set email alerts
|

Plzf regulates limb and axial skeletal patterning

Abstract: The promyelocytic leukaemia zinc finger (Plzf) protein (encoded by the gene Zfp145) belongs to the POZ/zinc-finger family of transcription factors. Here we generate Zfp145-/- mice and show that Plzf is essential for patterning of the limb and axial skeleton. Plzf inactivation results in patterning defects affecting all skeletal structures of the limb, including homeotic transformations of anterior skeletal elements into posterior structures. We demonstrate that Plzf acts as a growth-inhibitory and pro-apoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
264
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(275 citation statements)
references
References 31 publications
10
264
1
Order By: Relevance
“…Remarkably, PLZFde®cient mice show no apparent disturbance in hematopoiesis but rather exhibit severe testicular dysfunction, among other defects (Barna et al, 2000;Hawe et al, 1996). Furthermore, cyclin A has recently been identi®ed as one PLZF target gene, and cyclin A subtypes are considered to possess regulatory functions in murine spermatogenesis (Ravnik and Wolgemuth, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, PLZFde®cient mice show no apparent disturbance in hematopoiesis but rather exhibit severe testicular dysfunction, among other defects (Barna et al, 2000;Hawe et al, 1996). Furthermore, cyclin A has recently been identi®ed as one PLZF target gene, and cyclin A subtypes are considered to possess regulatory functions in murine spermatogenesis (Ravnik and Wolgemuth, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, PLZF is expressed in several human tissues, among them the testis (Zhang et al, 1999). Of note, PLZF null mice neither display any apparent disturbance of hematopoiesis nor develop leukemia but instead show defects in limb and axial skeletal patterning (Barna et al, 2000) and in spermatogenesis and testis development (Hawe et al, 1996). We report here that cORF, a protein encoded by human endogenous retroviruses transcribed in germ cell tumors, interacts with the PLZF transcriptional repressor.…”
Section: Introductionmentioning
confidence: 99%
“…It is a transcriptional repressor that inhibits stem cell differentiation and helps maintaining their presence in the niche. Plzf was originally identified in hematopoietic stem cells, but is also crucial for the patterning of the axial skeleton and the limbs (Reid et al, 1995;Barna et al, 2000). Plzf expression is high in undifferentiated multipotential hematopoietic progenitor cells, and low in differentiated cells (Reid et al, 1995).…”
Section: Etv5 and Other Transcription Factorsmentioning
confidence: 99%
“…Several reports show that PLZF induces growth suppression, apoptosis, and cell cycle arrest [7,8,23]. Analysis of PLZF knock-out mice revealed that the protein is a growth inhibitory and proapoptotic factor in the limb bud in vivo [35]. Interestingly, treatment with cannabinoids or overexpression of PLZF inhibits growth of prostate cancer cells [36][37][38].…”
Section: Discussionmentioning
confidence: 99%